2016
DOI: 10.1007/s10495-016-1218-5
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of α-synuclein in cerebral cortex improves neural behavior associated with apoptotic inhibition and neurotrophin expression in spinal cord transected rats

Abstract: Spinal cord injury (SCI) often causes severe functional impairment with poor recovery. The treatment, however, is far from satisfaction, and the mechanisms remain unclear. By using proteomics and western blot, we found spinal cord transection (SCT) resulted in a significant down-regulation of α-synuclein (SNCA) in the motor cortex of SCT rats at 3 days post-operation. In order to detect the role of SNCA, we used SNCA-ORF/shRNA lentivirus to upregulate or knockdown SNCA expression. In vivo, SNCA-shRNA lentiviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…In agreement with the finding that ␣-syn ablation might be neuroprotective, previous studies have shown that knocking down ␣-syn protects experimental models from the toxic effects of MPTP (Drolet et al, 2004;Javed et al, 2015), 3-nitropropionic acid , and spinal cord injury (Wang et al, 2016). The mechanisms through which reducing ␣-syn might protect neuronal populations from selected injuries or toxins such as A␤ oligomers are not completely understood.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In agreement with the finding that ␣-syn ablation might be neuroprotective, previous studies have shown that knocking down ␣-syn protects experimental models from the toxic effects of MPTP (Drolet et al, 2004;Javed et al, 2015), 3-nitropropionic acid , and spinal cord injury (Wang et al, 2016). The mechanisms through which reducing ␣-syn might protect neuronal populations from selected injuries or toxins such as A␤ oligomers are not completely understood.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, previous studies in DLB and ␣-syn Tg models have shown that ␣-syn aggregates disrupt endocytic and secretory pathways via abnormal interactions with Rab3A, Rab5, and Rab8 (Eisbach and Outeiro, 2013;Wang et al, 2014). These alterations can be reversed by overexpression of Rab1, Rab3a, and Rab11.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although the mechanism underlying apoptosis in Spag6 mutant SGNs needs further investigation, increased expression of Bax and the ratio of Bax and Bcl-2, the uneven distribution of cytochrome c and activated caspase 9 and 3 positive staining suggests that apoptosis was mediated through the mitochondrial pathway. Interestingly, Bcl-2 was not changed or increased significantly between the two groups, although Bax and Bcl-2 often show opposite trends in apoptosis related models 22 , 23 . Therefore, it seems that Spag6 increases Bax to alter the balance between Bax and Bcl-2, rather than decreasing Bcl-2.…”
Section: Discussionmentioning
confidence: 84%
“…SCI is one of the major causes of death and disability in clinical situations. It creates enormous psychological and economic burdens to an individual's family as well as the society as a whole (Guo et al, 2014;Du et al, 2015;Lu et al, 2015;Wang et al, 2016;Yang and Wang, 2015). In the United States, there are approximately 282,000 people suffering from SCI with an average growth of 17,000 cases annually (Jalan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%